(untitled) (Global Journal of Science Frontier Research, 2023)
A combined mechanism of nonequilibrium dislocation growth of crystal faces combined with equilibrium formation of a two-dimensional nucleation is presented. The binding energy of atoms in the crystal near the helical dislocation has been calculated based on the Lennard-Jones potential. The study substantiates thermodynamic conditions for the occurrence of hollow dislocation nuclei detected earlier in AFM observations of crystal growth. Conditions for the linear Onsager approximation in response to non-linear kinetics of crystal growth are described. The three values of solution supersaturation, the relationships between which are highly variable, are controlling the growth process of the crystal face. The supersaturation and their interrelations depend on the peculiarities of the defective crystal structure, the of the crystal-solution interaction, and the peculiarities of the crystallization medium hydrodynamics.